Genome-wide identification and expression analysis of the ZF-HD gene family in pea (Pisum sativum L.) - Shi, Bowen; Haq, Inzamam Ul; Fiaz, Sajid; Alharthi, Badr; Xu, Ming-Long; Wang, Jian-Lin; Hou, Wei-Hai; Feng, Xi-Bo (Frontiers in Genetics, 2023)
Pea is a traditional grain-feed-grass crop in Tibet and the only high-protein legume in the region, which plays an important role in Tibetan food and grass security. Zinc finger-homeodomain (ZF-HD) belongs to a family of homozygous, heterozygous cassette genes, which play an important role in plant growth, development, and response to adversity stress. 18 PsZF-HD family members were discovered using a bioinformatics approach, distributed across seven chromosomes and two scaffold fragments. Evolutionary analysis divided them into two subgroups, MIF and ZHD. The MIF subgroup was subdivided into three subclasses (PsMIFⅠ-Ⅲ), and the ZHD subgroup was subdivided into five subclasses (ZHDⅠ-V). The PsZF-HD members were named PsMIF1- PsMIF4 and PsZHD1- PsZHD14. MIF contains only one type of structural domain, while ZHD comprises two types of structural domains. 12 conserved motifs were identified in Motif; genes in the same class have similar motifs and protein 3D structures. Most PsZF-HD genes had no introns (13/18), and only 5 genes had 1 intron. Forty-five cis-acting elements were predicted and screened, containing four categories: light response, stress, hormone, and growth and development. Transcriptome analysis of different tissues during pea growth and development showed that PsZHD11, 8, 13, 14, and MIF4 were not expressed or were individually low expressed in tissues, while the other 13 PsZF-HDs genes were differentially expressed and showed tissue preference, as shown by aboveground reproductive organs, PsZHD6, 2, 10 and MIF1 (except immature seeds) were significantly highly expressed; in above ground In the aboveground nutritional organs, PsZHD6, 1 and 10 were significantly overexpressed; in the underground root system, PsMIF3 was specifically overexpressed. The leaf transcriptome under a low nitrogen environment showed that the expression of 17 PsZF-HDs members was upregulated in shoot organs. The leaf transcriptome under a low-temperature environment showed stress-induced up-regulation of PsZHD10 and 1 genes, while PsZHD6 was down-regulated. The above results lay the foundation for deeper exploration of PsZF-HD gene functions and also improve the reference for molecular breeding for stress resistance in peas.